COVID-19 pandemic impact on e-learning adoption and its utilization at higher education: a comparative analysis of institutions and students' perspectives - Farah Ali, Abdifatah; Abdullah, Rusli; Abi Hassan, Abdikarim; Abdullahi, Husein Osman; Mohamed, Mohamed Mohamud (International Information and Engineering Technology Association, 2024)
COVID-19 has forced Somali universities to implement e-learning systems to ensure education continuity. This study identifies the components that drive the effectiveness of e-learning platforms within Somali private universities by utilizing insights from student feedback. To accomplish this, the study employed the renowned DeLone and McLean's Information Systems Success (D&M IS) model, serving as a framework for evaluating and validating the factors pertaining to the e-learning platform's success. A questionnaire has been employed with the aim of gathering data from students to satisfy the research's objectives. In this study, 867 respondents were collected and analyzed using a structural equation model (SEM). Additionally, the results showed that Service Quality (SRQ), System Use (SU), System Quality (SQ), and User Satisfaction (US) significantly influenced Net Benefit (NB) of the e-learning platforms. However, there was no correlation between Information Quality (IQ) and User Satisfaction (US). This study provides useful insight to guide policy decisions and support e-learning. However, the study is limited since it is narrowly focused on Somalia, which limits its generalizability to other developing countries.